Engines of Growth in China: The Limits of Informal Institutions. Issue 1 (2nd January 2020) - Cunningham, Christopher; Dibooglu, Sel
Abstract: Since the 1978 reforms, China has experienced rapid economic and social development. GDP growth has been in the double digits on average yearly, creating the fastest sustained economic growth recorded by a major economy in history. Not only did this transform the economy and society at large, China reached important milestones in terms of reducing poverty and creating prosperity in a short period of time. This article uses the conceptual framework of new institutional economics to examine China's economic growth and how growth has been achieved largely by 'informal institutions' that are grounded in culture, customs, and private interactions that emerge spontaneously. The trajectory by which these informal institutions left their imprint on China's complex economic landscape and how they can constrain future economic growth are also of central importance. After examining decentralization and risk management practices, property rights, and the legal system, we emphasize the importance of creating formal institutions necessary for long-term growth, most importantly innovation. Preliminary evidence shows total factor productivity is tapering off which may reflect the constraints of China's institutional environment. This ought to be reversed if China is to enjoy long-term sustained growth.